Effect of the Intensity of Grazing on Root Growth of Grasses in the Grasslands of Upper Damodar Catchment - Pandey, S.N.; Singh Teotia, S.P.; Guha, D.P. (Journal of Soil and Water Conservation, 2022)
The prevailing practice of over-grazing in the Upper Damodar Catchment has denuded the grasslands of its superior species and exposed the land surface to the erosion hazards. As a result of overgrazing, the better species have been replaced by the inferior ones in the process of retrogressive changes. Under the over-grazed conditions, the grass-lands are ecologically in poor condition.According to Dabadghao 1957 in the Sehima-Dicanthium grassland type of this region, the poor condition represents a dominating stand of worthless annuals like Aristida species, Eragrostis species, Gracilea royleana, Urochloa panicoides, Dactyloctenium eagypticum, Oropetium thomacum, Brachiaria ramosa, Tragus racemosus, and Alleteropsis Cimicina together representing 75 percent of the total stand. Other species namely Sehima nervosum, Chrysopogon montanus, Dicanthium annulatum or Iseilema species, Botimocnica pertusa and Elemopogon foveolatus would be present in dying condition. The plant cover would be 5 to 25 per cent and the species comprising the 75 per cent stand are of very little fodder value.The forage yield available as estimated earlier under over-grazed condition at Deochanda Experiment Stations is very low producing 1866 pounds green matter per acre. The grasslands due to poor ground cover encourage more soil and water loss during the months from June to October being the critical period for erosion since most of the total rainfall is received during this period (Table 1). It has been found out at Deochanda Experiment Station by Mirchandani etal' 1956, that the soil loss from protected, properly grazed and overgrazed plots was 521, 765 and 2929 pounds per acre-respectively.